2012
DOI: 10.1186/1471-2407-12-200
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone prevents repopulation of ovarian cancer cells escaping cisplatin-paclitaxel therapy

Abstract: BackgroundAdvanced ovarian cancer is treated with cytoreductive surgery and combination platinum- and taxane-based chemotherapy. Although most patients have acute clinical response to this strategy, the disease ultimately recurs. In this work we questioned whether the synthetic steroid mifepristone, which as monotherapy inhibits the growth of ovarian cancer cells, is capable of preventing repopulation of ovarian cancer cells if given after a round of lethal cisplatin-paclitaxel combination treatment.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 58 publications
(81 reference statements)
1
71
0
Order By: Relevance
“…Telleria et al . previously reported that mifepristone treatment of OvCa cell lines at the much higher concentrations of 10-20 μM (versus 1 μM used in our studies) causes cell cycle arrest (27) and cytostasis (28). These authors also noted that the growth inhibitory effect of mifepristone did not require PR expression.…”
Section: Discussionmentioning
confidence: 54%
“…Telleria et al . previously reported that mifepristone treatment of OvCa cell lines at the much higher concentrations of 10-20 μM (versus 1 μM used in our studies) causes cell cycle arrest (27) and cytostasis (28). These authors also noted that the growth inhibitory effect of mifepristone did not require PR expression.…”
Section: Discussionmentioning
confidence: 54%
“…Anti-tumor effect can be improved if this process could be effectively inhibited. Previous studies of ours and others demonstrated that specific inhibitors and immunoenhancing agents can inhibit cancer cell repopulation in a variety of cancers in animal models [4][5][6]. This concept has been applied to malignant pleural mesothelioma (MPM), which is a rare but aggressive cancer with poor prognosis.…”
Section: Introductionmentioning
confidence: 88%
“…The fact that celecoxib is efficacious in improving chemotherapeutic response in a primary xenograft model derived from an original patient who failed chemotherapy, this provided convincing proof-of-concept evidence for testing such adjuvant therapeutic approaches with comparable concepts in other preclinical models and subsequent human clinical trials. Indeed, other approaches that block tumor repopulation (although not specifically targeting cancer stem cells) has been proven effective to enhance chemotherapeutic response in xenograft models of ovarian (3537), glioma (38), breast (39, 40), prostate cancer (40) and mesothelioma (41). …”
Section: Clinical-translational Advancesmentioning
confidence: 99%